2021
DOI: 10.7759/cureus.20775
|View full text |Cite
|
Sign up to set email alerts
|

Withania somnifera as an Adjunctive Treatment for Refractory Restless Legs Syndrome in Parkinson’s Disease: A Case Report

Abstract: Non-motor symptoms of Parkinson's disease (PD), such as insomnia and restless legs syndrome (RLS), tend to worsen and become refractory as neurodegeneration progresses. We report the case of a 72-year-old female with a six-year history of PD and two-and-half-year history of insomnia and refractory RLS. We added a neuroprotective agent, Withania somnifera, to the existing treatment regimen for her insomnia. Besides the partial remission of her insomnia and motor symptoms of PD, there was a complete reversal of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(15 reference statements)
0
1
0
1
Order By: Relevance
“…Chaudhari KS et al ( 2021) opisuje przypadek 72-letniej kobiety cierpiącej z powodu choroby Parkinsona poddanej 2-miesięcznej suplementacji ashwagandą w celu terapii bezsenności. Oprócz częściowego ustąpienia zaburzeń snu, nieznacznego zmniejszenia się drżenia mięśniowego oraz sztywności, u pacjentki zaobserwowano całkowite ustąpienie objawów zespołu niespokojnych nóg [8].…”
Section: Badania Na Ludziachunclassified
“…Chaudhari KS et al ( 2021) opisuje przypadek 72-letniej kobiety cierpiącej z powodu choroby Parkinsona poddanej 2-miesięcznej suplementacji ashwagandą w celu terapii bezsenności. Oprócz częściowego ustąpienia zaburzeń snu, nieznacznego zmniejszenia się drżenia mięśniowego oraz sztywności, u pacjentki zaobserwowano całkowite ustąpienie objawów zespołu niespokojnych nóg [8].…”
Section: Badania Na Ludziachunclassified
“…Potential neuroprotective effects of various active constituents of WS have been studied in toxin-induced animal models of PD [4,17], together with their effects on mitochondrial dysfunctions [5,18], neuroinflammation [17], and motor impairment [6,17,18]. Moreover, studies in PD patients have revealed that WS administration caused a complete remission of treatment-refractory restless leg syndrome [19]. The mechanisms proposed for the observed therapeutic effects of WS in experimental models of PD and parkinsonian patients, similarly to those proposed for studies of AD, involve an enhanced bioavailability of antioxidant agents (i.e.…”
Section: Introductionmentioning
confidence: 99%